ANALYSIS AND RISK ASSESSMENT OF THE PROJECT "SOUTH STREAM" ON THE TERRITORY OF THE REPUBLIC OF SERBIA. - D. V. Shamin (Real Economics Publishing House, 2014)
The article focuses on the identification, qualitative and quantitative risk assessment, make recommendations for non-insurance risk mitigation techniques, the development of the insurance program оbjects of the gas pipeline “South Stream”.